Caspase-2 and oxidative stress underlie the immunogenic potential of high hydrostatic pressure-induced cancer cell death. (2nd January 2017) - Moserova, Irena; Truxova, Iva; Garg, Abhishek D.; Tomala, Jakub; Agostinis, Patrizia; Cartron, Pierre Francois; Vosahlikova, Sarka; Kovar, Marek; Spisek, Radek; Fucikova, Jitka
ABSTRACT: High hydrostatic pressure (HHP) promotes key characteristics of immunogenic cell death (ICD), in thus far resembling immunogenic chemotherapy and ionizing irradiation. Here, we demonstrate that cancer cells succumbing to HHP induce CD4 + and CD8 + T cell-dependent protective immunity in vivo . Moreover, we show that cell death induction by HHP relies on the overproduction of reactive oxygen species (ROS), causing rapid establishment of the integrated stress response, eIF2α phosphorylation by PERK, and sequential caspase-2, −8 and −3 activation. Non-phosphorylatable eIF2α, depletion of PERK, caspase-2 or −8 compromised calreticulin exposure by cancer cells succumbing to HHP but could not inhibit death. Interestingly, the phagocytosis of HHP-treated malignant cells by dendritic cells was suppressed by the knockdown of caspase-2 in the former. Thus, caspase-2 mediates a key function in the interaction between dying cancer cells and antigen presenting cells. Our results indicate that the ROS→PERK→eIF2α→caspase-2 signaling pathway is central for the perception of HHP-driven cell death as immunogenic.